Preserving Cultural Identity through Architecture: A Case Study of Traditional Tenganan Village (Desa Adat) - Suci Elvira; Endah Harisun; Haryati (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
This research investigates the role of architecture in preserving cultural identity through a case study of Tenganan Customary Village. The village features rich traditional architecture with distinctive cultural values. Through the use of traditional building materials, unique architectural features, organized spatial arrangement, cultural activities, rituals, and active community involvement, the cultural identity of Tenganan Village has been successfully maintained and preserved. The study employs a qualitative approach, incorporating literature review, field survey, and interviews as data collection methods. The research findings highlight the significant role of architecture in cultural identity preservation, with active community participation being a key factor in sustaining the culture. These findings offer valuable insights for policymaking and practices in preserving cultural identity through architecture, not only in Tenganan Customary Village but also in other regions with rich cultural heritage.